Self-Assembly of Semiconducting Polymer Amphiphiles for In Vivo Photoacoustic Imaging - Xie, Chen (2017)
Despite the advantages of semiconducting polymer nanoparticles (SPNs) over other inorganic nanoparticles for photoacoustic (PA) imaging, their synthetic method is generally limited to nanoprecipitation, which is likely to cause the issue of nanoparticle dissociation. The synthesis of near-infrared (NIR) absorbing semiconducting polymer amphiphiles (SPAs) that can spontaneously self-assemble into homogeneous nanoparticles for in vivo PA imaging is reported. As compared with their counterpart nanoparticles (SPN1) prepared through nanoprecipitation, SPAs generally have higher fluorescence quantum yields but similar size and PA brightness, making them superior over SPN1. Optical and simulation studies reveal that the poly(ethylene glycol) (PEG) grafting density plays a critical role in determining the packing of SP segments inside the core of nanoparticles, consequently affecting the optical properties. The small size and structurally stable nanostructure, in conjunction with a dense PEG shell, allow SPAs to passively target tumors of living mice after systemic administration, permitting both PA and fluorescence imaging of the tumors at signals that are ≈1.5-fold higher than that of liver. This study thus not only provides the first generation of amphiphilic optically active polymers for PA imaging, but also highlights the molecular guidelines for the development of organic NIR imaging nanomaterials.